PELATIHAN PENGENALAN TEKNOLOGI LINE FOLLOWER ROBOT BAGI SISWA-SISWI SEKOLAH MENENGAH ATAS REGINA PACIS SURAKARTA - Siswoyo, Agus; Arianto, Eko; Noviyanto, Antonius Hendro (Universitas Sanata Dharma, 2023)
A robot is a technology that is currently developing rapidly. Robot technology is a technology that applies multi-disciplinary science. This service activity aims to introduce robot technology to high school/equivalent students so that they can apply and implement science, informatics, and mathematics that have been obtained in high school lessons. The method used in this training is to provide intensive assistance and training to the trainee students. It is hoped that with the method used, high school students can more easily find simple robot technology and apply it to the robot that will be made. In this training, students will be introduced to Line Follower Robot technology.